Microenterprise and applied corporate social responsibility - Mendoza-Woodman, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Corporate social responsibility (CSR) is recognized as having a positive impact on business performance, mainly in large companies, but its sustainability in SMEs is debated. This article proposes a CSR model for SMEs based on a literature review and then examined in a group of microenterprises that practice CSR. Through narrative analysis it was found that it is feasible to carry out CSR actions in these businesses, but family, collaborative work and institutional support must be considered as additional factors that influence its sustainability.